## 2x – 4 = -4 (x – 5)

### To solve the equation 2x – 4 = -4(x – 5), we will first distribute -4 to the terms inside the parentheses:

2x – 4 = -4x + 20

To solve the equation 2x – 4 = -4(x – 5), we will first distribute -4 to the terms inside the parentheses:

2x – 4 = -4x + 20.

Next, we will combine like terms by adding 4x to both sides:

2x + 4x – 4 = -4x + 4x + 20.

This simplifies to:

6x – 4 = 20.

To isolate the variable x, we will add 4 to both sides:

6x – 4 + 4 = 20 + 4.

This gives:

6x = 24.

Finally, to solve for x, we divide both sides by 6:

6x/6 = 24/6.

This simplifies to:

x = 4.

Therefore, the solution to the equation 2x – 4 = -4(x – 5) is x = 4.

Definition:

Equation – An equation is a mathematical statement that sets two expressions equal to each other. It typically contains an unknown variable that we are trying to solve for. The goal is to find the value(s) of the variable that make the equation true.

##### More Answers:

Calculating the Product of Negative Numbers | (-9) multiplied by (-7) yields 63Solving the Equation 2(3x + 1) = 7x – 5 | Step-by-Step Math Solution

Solving Equations | Isolating Variables to Find Solutions